2020
DOI: 10.1177/1052562920937031
|View full text |Cite
|
Sign up to set email alerts
|

Gender Equality in International Business Education

Abstract: The United Nations established gender equality as a top priority in its international agenda, and many stakeholders around the world have joined the effort to build a fair playing field for all. Business educators can contribute to this effort by delineating problem areas in gender equality in international business education, uncovering ways to address such problems, and inquiring into the most basic premises we entertain in this quest. Our contribution to this international agenda involves a review of the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Although women tend to be better educated, they are often disadvantaged in complex entrepreneurial environments [4,5]. Introducing gender-sensitive education can promote women's entrepreneurship and support gender equality [6,7]. We investigate how women's entrepreneurial education relates to digitalisation, innovation and sustainability using a scientometric approach.…”
Section: Introductionmentioning
confidence: 99%
“…Although women tend to be better educated, they are often disadvantaged in complex entrepreneurial environments [4,5]. Introducing gender-sensitive education can promote women's entrepreneurship and support gender equality [6,7]. We investigate how women's entrepreneurial education relates to digitalisation, innovation and sustainability using a scientometric approach.…”
Section: Introductionmentioning
confidence: 99%
“…But how much do we actually know about gender-related practices in business teaching? Wagstaff et al (2020) found in their review of gender-related content in the field of international business (IB) a "complete absence of articles dedicated to teaching and learning in relation to gender equality in international business education" (p. 612). We address this gap by reporting the findings of a study on the use of simulations in two undergraduate business programs, the results of which highlight gendered perceptions of learning.…”
Section: Introductionmentioning
confidence: 99%
“…In our role as entrepreneurship educators, we asked ourselves what business and management educators in higher education institutions (HEIs) can do to inspire students and scientists who seemingly do not fit the masculine entrepreneurial ideal to consider entrepreneurship as a desirable career for themselves, thereby addressing gender inequalities in labor markets (Knipfer et al, 2017; Simpson, 2006; Wagstaff et al, 2020). The many efforts to promote greater diversity in entrepreneurship that have been implemented by educators in HEIs around the world have focused primarily on women and the design of educational interventions tailored to their needs (Botha et al, 2006; Bullough et al, 2015; Elliott et al, 2020).…”
Section: Introductionmentioning
confidence: 99%